Non-adherence to antidementia medications and associated factors: a study of Spanish population-based registry data - Gutiérrez-Abejón, Eduardo; Pedrosa-Naudín, M. Aránzazu; Fernández-Lázaro, Diego; Díaz Planelles, Isabel; Álvarez, F. Javier (Frontiers in Pharmacology, 2024)
With an increasing prevalence, dementia is one of the most disabling diseases among the elderly. Impaired cognitive function and behavioral and psychological symptoms predispose patients to medication non-adherence, resulting in increased morbidity, mortality, and healthcare costs. The aim of this study was to estimate the prevalence of non-adherence to antidementia medications and to identify the main predictors. A population-based registry study was conducted in 2022 in Castile and Leon, Spain to estimate the prevalence of non-adherence to antidementia medications. A total of 17563 patients with dementia were included. The medication possession ratio (MPR) was used as an indirect method to measure adherence. The cut-off point for determining that a patient was nonadherent was 80% of MPR. Multivariate logistic regression was used to identify predictors of nonadherence based on sociodemographic and health-related variables. In 2022, 6.2% of the population over 80 years old used antidementia medications. Of these patients, 70% were women, 28.15% were institutionalized, and over 90% were polymedicated and had multiple prescribers. The most used medicines were donepezil (43.49%), rivastigmine (36.84%), and memantine (30.7%). The combined use of an acetylcholinesterase inhibitor plus memantine was relevant (13.33%). Men were less adherent than women, and the prevalence of non-adherence decreased with age. The medication associated with the highest prevalence of non-adherence was rivastigmine (19%), followed by donepezil (17%) and memantine (13.23%). Institutionalized patients (13%) and patients on combination therapy (13.29%) had the lowest prevalence of non-adherence. Protective factors against non-adherence include institutionalization, polymedication, use of memantine or combination therapy, and comorbid mental illness. In Castile and Leon, oOne in six patients were non-adherent to antidementia medications. Having a reliable indicator to identify non-adherent patients is essential for appropriate pharmacotherapeutic follow-up of patients. MPR is a widely used tool in our healthcare system for identifying early non-adherence issues. Younger male patients with cardiometabolic disease are more likely to be non-adherent to antidementia medications. On the other hand, institutionalization is a protective factor against non-adherence, but still 10% of nursing home patients are non-adherent to antidementia medications.